Researcb on tbe Tecbnology of Application-Oriented Cloud Data Center Network - Nan Chen; Yongbing Fan; Xiaowu He; Yi Liu; Zhilan Huang (Dianxin kexue)
The architecture of application-oriented cloud data center network, which is application-aware, network programmable, network virtualization, flexible and high available was proposed. The key technologies and their applications in each layer were analyzed. The proposed network architecture meets the requirements of data center network for cloud computing.